Late-onset sepsis in very low birth weight preterm infants: 7 years' experience at a tertiary hospital in China - Liya Ma; Qiongling Peng; Wei Wang; Yi Yang; You Chen; Liling Wang; Hung-Chih Lin (Pediatrics and Neonatology)
Objective: Studies about the epidemiology and risk factors of late onset of sepsis (LOS) in preterm very low birth weight (PVLBW) infants of developing countries are limited and variable. The objective of this study was to explore the epidemiology, risk factors and pathogens of LOS in VLBW infants in a Chinese tertiary hospital. Methods: Data concerning demographies, pathogens, risk factors and outcomes of LOS were collected in a cohort of 710 VLBW infants discharged from January 2012 to December 2018. Chi-square, t-test and multivariable logistic regression analysis were used to identify risk factors. Results: The overall incidence of LOS was 24.08% and blood culture-proven sepsis was 19.58%. Gram-negative bacteria accounted for 57.93%, and 32.41% of the isolates were Klebsiella pneumoniae. LOS led to a longer hospital stay, higher hospitalization cost and higher mortality compared to infants without LOS. Mortality in Gram-negative or fungi LOS was higher than in Gram-positive LOS. The factor of PVLBW infants with registered permanent residence (PR) was associated with 80% lower likelihood of LOS compared to those without registered PR (P = 0.000, 95% CI 0.096–0.420). Infants with thrombocytopenia had 2.5 times LOS of control (P = 0.014, CI 1.210–5.132). Duration of parenteral nutrition was a risk of LOS (P = 0.009, CI 1.010–1.069). Conclusion: Gram-negative bacteria, especially Klebsiella pneumonia, were the dominant pathogens in this study. Social factors might be a risk of LOS in PVLBW infants in developing countries. Taking measures to reduce the duration of parenteral nutrition may be helpful in decreasing the incidence of LOS. Awareness of thrombocytopenia may help to recognized diagnosis of LOS.